2019
DOI: 10.1136/jnnp-2018-320155
|View full text |Cite
|
Sign up to set email alerts
|

CSF neurogranin as a neuronal damage marker in CJD: a comparative study with AD

Abstract: ObjectiveTo investigate whether cerebrospinal fluid (CSF) neurogranin concentrations are altered in sporadic Creutzfeldt-Jakob disease (CJD), comparatively with Alzheimer’s disease (AD), and associated with neuronal degeneration in brain tissue.MethodsCSF neurogranin, total tau, neurofilament light (NFL) and 14-3-3 protein were measured in neurological controls (NCs, n=64), AD (n=46) and CJD (n=81). The accuracy of neurogranin discriminating the three diagnostic groups was evaluated. Correlations between neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 51 publications
8
57
4
Order By: Relevance
“…Unexpectedly 14‐3‐3 resulted a significant predictor of CTh values while other neurodegeneration markers as T‐tau, NfL, and Ng did not. Previous studies have analyzed the contribution of Aβ and T‐tau to structural changes in AD (Blennow et al, ; Li et al, ; Tosun, Schuff, Shaw, et al, ). The relevant contribution of Aβ in the CTh AD signature in the present study is plausible given its main role in AD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly 14‐3‐3 resulted a significant predictor of CTh values while other neurodegeneration markers as T‐tau, NfL, and Ng did not. Previous studies have analyzed the contribution of Aβ and T‐tau to structural changes in AD (Blennow et al, ; Li et al, ; Tosun, Schuff, Shaw, et al, ). The relevant contribution of Aβ in the CTh AD signature in the present study is plausible given its main role in AD pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
“…CSF NfL levels have proved especially useful differentiating FTLD from early‐onset AD given that NfL levels in AD are lower in early onset compared to those in late onset presentations (Alcolea, Vilaplana, Suárez‐Calvet, et al, ; Olsson, Portelius, Cullen, et al, ; Portelius et al, ; Sjögren, Rosengren, Minthon, et al, ). Neurogranin (Ng) is a synaptic (dendritic) marker that has been suggested to be specific for AD although increased levels are also found in Creutzfeldt–Jakob diseases (Blennow, Diaz‐Lucena, Zetterberg, et al, ; Gaetani, Blennow, Calabresi, et al, ; Wellington et al, ). The 14‐3‐3 protein has been extensively studied in Creutzfeldt–Jakob disease, but its participation on the AD neuropathological process has also been described (Burkhard, Sanchez, Landis, et al, ; Chohan et al, ; McFerrin, Chi, Cutter, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, synaptic integrity and function are both the growing concerns in the pathogenesis of a wide variety of neurological and mental diseases ( Fyfe, 2015 ; Hellwig et al, 2015 ; Yang et al, 2015 ; Zetterberg and Blennow, 2015 ; Bereczki et al, 2017 ; De Vos et al, 2017 ; Guha et al, 2018 ; Blennow et al, 2019 ). In animal experiments, it showed that mice lacking NRGN show a remarkable decline in hippocampus-dependent spatial memory and deficits in hippocampal long-term potentiation ( Pak et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…The elevation of CSF Ng seems to be specific for AD and is not seen in other neurodegenerative disorders beside CJD [52,63,64]. A recent study examining postmortem parietal and temporal cortex tissues found that the ratio of peptide-to-total full-length Ng was higher in patients with AD compared to controls, suggesting increased processing of Ng into peptides [65].…”
Section: Csf Neurograninmentioning
confidence: 97%
“…High levels of NfL are also seen in other neurodegenerative disorders, such as amyotrophic lateral sclerosis (ALS), HIV-associated dementia (HAD) and Creutzfeldt-Jakob disease (CJD) [51]. In addition to very high NfL levels seen in CJD, the rapidly progressive disease exhibits unique, multi-fold increase in concentration of multiple other CSF biomarkers, including total tau, alpha-synuclein and neurogranin [52][53][54].…”
Section: Csf and Blood Nflmentioning
confidence: 99%